Carbon‐Tailored Semimetal MoP as an Efficient Hydrogen Evolution Electrocatalyst in Both Alkaline and Acid Media. Issue 24 (25th June 2018) - Li, Guowei; Sun, Yan; Rao, Jiancun; Wu, Jiquan; Kumar, Anil; Xu, Qiu Nan; Fu, Chenguang; Liu, Enke; Blake, Graeme R.; Werner, Peter; Shao, Baiqi; Liu, Kai; et al.
Abstract: The electrolysis processes such as hydrogen evolution reaction (HER) require high efficient catalysts with robust surface stability. A high conductivity is also necessary to speed up the charge transport between the catalyst and the electrolyte. Recently, the observation of exceedingly high conductivity in the topological semimetal MoP, has provided a model catalyst to investigate the correlation between the electrical transport and the electrocatalytic activity for the HER. Thus, MoP is encapsulated in a Mo, P codoped carbon layer (MoP@C). This composite material exhibits outstanding HER performance, with an extremely low overpotential of 49 mV at a current density of 10 mA cm −2 and a Tafel slope of 54 mV dec −1 in an alkaline medium. In addition, electron transport analysis indicates that MoP exhibits high conductivity and mobility due to the existence of triple‐point fermions and a complex Fermi surface. Furthermore, the presence of PC and MoC bonds at the interface between the carbon layer and the MoP particles modulates the band structure of MoP@C and facilitates fast electron transfer, accumulation, and subsequent delocalization, which are in turn responsible for the excellent HER activity. Abstract : Topological semimetals such as MoP have unique surface states that are topologically protected and robust. The ultrahigh mobility and conductivity originates from the linear dispersion of the band structure. The formation of MoC and PC bonding can reshape the band structure of MoP@C, thereby favoring electron transfer and delocalization, and allowing this material to be applied as an electrocatalyst.